A comprehensive review and case series of adjuvant and neoadjuvant therapies in acral melanoma with emerging insights from CT DNA testing - Rao, Adityanarayan; Mathavan, Akash; Mathavan, Akshay; Doonan, Bentley (Frontiers in Oncology, 2025)
IntroductionAcral melanoma is a rare but aggressive type of skin cancer that appears on the hands, feet, and under the nails. Unlike other melanomas, it is not linked to sun exposure and has unique genetic features that may require different treatment strategies. This research aims to explore whether immunotherapy given before surgery (neoadjuvant therapy) or after surgery (adjuvant therapy) is more effective in improving patient outcomes.MethodsBy analyzing existing studies, we hope to understand which approach better reduces the risk of cancer returning and improves survival.ResultsFurther, we assessed the clinical course and outcomes of adjuvant and neoadjuvant immunotherapy through a case series of five patients who underwent either intervention. Additionally, we examine how new blood tests that detect tumor DNA could help track treatment response and personalize therapy.DiscussionOur findings may guide doctors in selecting the best treatment plans, leading to improved care for patients with this challenging disease and advancing research into more effective therapies.